Designing and Building Web Framework -Case study: Master registration website - Chikha, Youcef; Djaballah, Souhaib; Kahla, Mohammed Elhabib (university of eloued جامعة الوادي, 2018)
ھناك العدید من منصات تطویر تطبیقات الویب للاختیار بالنسبة للمطورین. یجب أن یكون لدى المطورون القدرة أو بناء إطار عمل خاص بھم حسب Django و Laravel على اتخاذ القرار بشأن استخدام منصة تطویر خارجیة مثل ما یناسب مشروعھم. یتطلب اختیار أنسب منصة تطویر لمشروع ما فھم جید لكیفیة عمل منصات التطویر في الخلفیة. تھدف ھذه الدراسة إلى توضیح وشرح مفھوم منصات تطویر تطبیقات الویب من خلال بناء منصة تطویر كاملة مع أحدث تقنیات الویب.There are many Web frameworks for developers to choose. The developers should have the ability to decide whether to use an external framework such as Laravel and Django or build their own framework that suits their project. Choosing the most suitable framework to use in a project requires a good understanding of how a framework actually works under the hood. This study aimed to demonstrate and explain the concept of Web frameworks by building a complete web framework using PHP with the latest web technologies.
licence mémoire informatique